Odpowiedzi

2010-03-08T22:02:10+01:00
{ x-y=0
{ x+y+z=4
{ x+2y+3z=9

{ x=y
{ y+y+z=4
{ y+2y+3z=9

{ x=y
{ z=4-2y
{ y+2y+3(4-2y)=9

{ x=y
{ z=4-2y
{ y+2y+12-6y=9

{ x=y
{ z=4-2y
{ 3y=-3

{ x=y
{ z=4-2y
{ y=-1

{ x=-1
{ z=4-2*(-1)=4+2=6
{ y=-1
2010-03-08T22:02:37+01:00
{ x-y=0
{ x+y+z=4
{ x+2y+3z=9

x=y

y+y+z=4
y+2y+3z=9

2y+z=4
3y+3z=9

z=4-2y
3y+3(4-2y)=9

z=4-2y
3y+12-6y=9

z=4-2y
-3y=-3

y=1
z=2
x=1
2010-03-08T22:06:42+01:00
{ x-y=0
{ x+y+z=4
{ x+2y+3z=9

x=y

y+y+z=4
y+2y+3z=9

2y+z=4
3y+3z=9

z=4-2y
3y+3(4-2y)=9

z=4-2y
3y+12-6y=9

z=4-2y
-3y=-3

odp.:y=1
odp.:z=2
odp.:x=1